1994
DOI: 10.1088/0953-8984/6/1/027
|View full text |Cite
|
Sign up to set email alerts
|

Raman and low frequency Raman spectroscopy of lead, zinc and barium metaphosphate glasses doped with Eu3+ions

Abstract: An investigation of low-frequency inelastic scattering (LOFIS) and pre-resonant Raman spectroscopy has revealed the role of the modifying cations, Ba2+, Zn2+ and Pb2+ on the bonding properties of the Eu-O bond in Ba(PO3)2, Zn(PO3)2, and Pb(PO3)2 glasses. Analysis of the results has shown that the electronegative character of the Pb2+ ions and the ionic radii of the Ba2+ and Zn2+ ions play a major role in the short-range order of the metaphosphate glasses. Furthermore, it was shown, using LOFIS, the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Several studies have shown that lead Phosphate glasses have got the best physical properties, such as high thermal expansion coefficients and low melting temperature. [6][7][8][9][10] The included lead oxide (PbO) provides a good chemical durability to the glassy network 11 which often enlarges their usefulness in many fields. 12 PbO can play the role of either network modifier or network former, 14 so it can be incorporated in large proportions in other glass network such as SiO 2 , B 2 O 3 and P 2 O 5 systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that lead Phosphate glasses have got the best physical properties, such as high thermal expansion coefficients and low melting temperature. [6][7][8][9][10] The included lead oxide (PbO) provides a good chemical durability to the glassy network 11 which often enlarges their usefulness in many fields. 12 PbO can play the role of either network modifier or network former, 14 so it can be incorporated in large proportions in other glass network such as SiO 2 , B 2 O 3 and P 2 O 5 systems.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the glass may be composed mainly of the pyrophosphate Q 1 and orthophosphate Q 0 groups (Q n : n is the number of bridging oxygen atoms by PO4 tetrahedron). A great similarity was found between the Raman spectra of A 2 2 and which can be assigned to symmetric stretching modes of P 2 O 7 groups indicates that the A 2 MnMP 2 O 10 glass structure is formed of a large amount of pyrophosphate. We note that the Raman bands near 920 cm −1 decrease in intensity and width in the order Li > Na > K, they can be assigned to symmetric vibrations of MO 6 octahedra (M = Mn, W, Mo).…”
Section: Ramanmentioning
confidence: 81%
“…They are characterized by low glass transition temperatures and high thermal expansion coefficients. These characteristics, allow them to be used for original applications: sealing glasses [1], oxidation resistant coatings, their interesting optical properties permit them to be operate as template for laser [2], waste containment matrixes. However, the use of these materials is limited by their low chemical durability.…”
Section: Introductionmentioning
confidence: 99%
“…At least two spectra for each sample were recorded in the wavenumber range of 400-2000 cm , corrected for dark-current noise and normalized. The resulted spectra were curving fitted (Proulx et al, 1994) to get quantitative values for the band areas of heavily overlapped bands. The curvefitting procedure is based on a least-squares minimization which in its turn involves entering the values of the wavenumber of the component bands (determined by using the deconvolution technique) and then a program determines the best estimate of the parameters of the component curves.…”
Section: Methodsmentioning
confidence: 99%